Gastronomic tourism, a differential factor - Cunha, Sandra (2018)
Introduction: Gastronomic Tourism has grown considerably worldwide and even at European level. According to the World Tourism Organization (UNWTO, 2012), the destinations and tourism companies are aware of the importance of gastronomy to diversify tourism and stimulate local, regional and national economic development. Gastronomy has always been part of the history of Portugal as a product that gave it authenticity and glamor. Objective: This article intends to make known the strategic product Gastronomy, as a tourist product of excellence with high development potential for Portuguese Tourism. Methods: We have analyzed several published studies correlating the main ideas and doctrines, focusing the importance of Gastronomic Tourism and gastronomic events for the development of regions and gastronomic routes as a differentiating factor. As well as the profile of gastronomic tourist, the phases of the experience of gastronomic tourism and gastronomic tourists behavior were analyzed. Results: there are some significant flaws in the literature review, since there are not many studies regarding the contribution of gastronomy to the development of the regions. Conclusions: Gastronomy is one of the tourist products that has the most influence when choosing the destination. Portugal should, like Spain and France, structure the gastronomy product as a product that gives Portugal authenticity and quality. The gastronomy and the wines are considered qualifying assets of the portuguese tourist offer (Estratégia Turismo 2027, 2017).